2004
DOI: 10.1111/j.1365-263x.2004.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity following dental treatment of children under intubation general anaesthesia in a day‐stay unit

Abstract: Pain following dental GA was the most prevalent and long lasting symptom of postoperative morbidity in this study. Reductions in operating time and improvement in pain control have the potential to reduce reported morbidity following dental GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
84
5
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 11 publications
14
84
5
6
Order By: Relevance
“…[25][26][27] There is not a clear explanation for this difference in gender distribution, but it has been suggested that a higher prevalence of neuropsychiatric disorders among boys could explain the predominance of males. 22 It has been reported that in hospital settings, the frequency of DGA is concentrated in patients affected with cardiac problems, asthma, physical and emotional disabilities.…”
Section: Discussionmentioning
confidence: 94%
“…[25][26][27] There is not a clear explanation for this difference in gender distribution, but it has been suggested that a higher prevalence of neuropsychiatric disorders among boys could explain the predominance of males. 22 It has been reported that in hospital settings, the frequency of DGA is concentrated in patients affected with cardiac problems, asthma, physical and emotional disabilities.…”
Section: Discussionmentioning
confidence: 94%
“…At 24 hr, the median (interquartile range [IQR]) NRS in both groups was 0 [1]. The NRS scores at 24 hr are shown in Figs.…”
Section: Resultsmentioning
confidence: 98%
“…In response to this sobering report, studies have attempted to measure postoperative morbidity 5 and local anesthesia has been looked upon favorably as a potential technique to improve outcomes with varying levels of success. 2 Jurgens et al 6 could not find a statistically significant difference in self-reported postoperative pain between children treated with local anesthetic compared with those treated with systemic analgesics (intravenous fentanyl and paracetamol [acetaminophen] either alone or in combination) for dental extractions, but subjectively determined that the children appeared ''more settled'' in recovery. Atan et al 2 reported that the odds of experiencing pain at the operation site were reduced by local analgesia by an odds ratio of 0.39, but these children were more likely to report dizziness.…”
mentioning
confidence: 99%
“…2 Jurgens et al 6 could not find a statistically significant difference in self-reported postoperative pain between children treated with local anesthetic compared with those treated with systemic analgesics (intravenous fentanyl and paracetamol [acetaminophen] either alone or in combination) for dental extractions, but subjectively determined that the children appeared ''more settled'' in recovery. Atan et al 2 reported that the odds of experiencing pain at the operation site were reduced by local analgesia by an odds ratio of 0.39, but these children were more likely to report dizziness. Two other studies found a significant benefit to intraligamental injection but only at one isolated time in the immediate postoperative period (5 minutes).…”
mentioning
confidence: 99%
See 1 more Smart Citation